2016
DOI: 10.1179/2047387715y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Investigating predictors and moderators of burnout in staff working in services for people with intellectual disabilities: the role of emotional intelligence, exposure to violence, and self-Efficacy

Abstract: Objectives Understanding predictors of burnout could potentially aid interventions for staff working in services for people with intellectual disabilities (ID). This study sought to understand predictors of burnout for staff specifically focusing on the moderating effect of emotional intelligence (EI) and self-efficacy.Methods 86 staff members working in services for people with ID completed a series of questionnaires about their experiences of violence, burnout (emotional exhaustion, depersonalisation and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…These results are in line with the Shead et al . () study. However, a study by Görgens‐Ekermans and Brand () found a moderating effect of EI in the job stress–burnout association.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are in line with the Shead et al . () study. However, a study by Görgens‐Ekermans and Brand () found a moderating effect of EI in the job stress–burnout association.…”
Section: Discussionmentioning
confidence: 97%
“…However, Shead et al . () investigated the moderating role of EI in the association between violence and burnout in a cross‐sectional study and found that EI did not moderate the association. It seems warranted to investigate whether EI is a moderator over time in the development of burnout symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, training (MacDonald & McGill, ) and improving staff rapport with service users (Magito‐McLaughlin & Carr, ; Willems, Embregts, Stams, & Moonen, ). Research on staff experiences has mostly focused upon negative aspects, for example, stress and burnout related to managing behaviours that are regarded as challenging (Rose et al, ; Shead, Scott, & Rose, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two important predictors of burnout in care settings are alexithymia (a lack of skills to identify and describe one's own emotions) and emotional intelligence (the ability to pay attention to, understand and regulate emotions) (Katsifaraki & Wood, ; Shead, Scott, & Rose, ). Although previous research has examined the association between alexithymia, emotional intelligence and burnout, we have found no studies examining these variables in nursing assistants (NAs) working in older adult care.…”
Section: Introductionmentioning
confidence: 99%
“…Although emotional intelligence may help to explain individual differences in the development of burnout (Görgens‐Ekermans & Brand, ), we have found no studies examining the relationship between emotional intelligence and burnout among NAs in the geriatric field. However, an inverse relationship between emotional intelligence and burnout is well established among staff who have direct contact with patients in residential care settings (Gerits, Derksen, & Verbruggen, ; Mikolajczak, Menil, & Luminet, ), with emotional intelligence being shown to be a significant predictor of low burnout (Shead et al, ) and more specifically of lower emotional exhaustion and personal accomplishment, showing a moderator effect in the stress‐burnout relationship (Görgens‐Ekermans & Brand, ; Salami & Ajitoni, ; Szczygieł & Bazińska, ). These findings suggest that individuals high in emotional intelligence would, because of their ability to identify and understand their emotions and to make use of emotional repair strategies, be able to reduce the impact of work stressors, thus protecting them against burnout.…”
Section: Introductionmentioning
confidence: 99%